Keragaman Permudaan Pohon di Area Sumber Air Blok Seda, Taman Nasional Gunung Ciremai: Diversity of tree seedlings in water springs area Seda Block, Mount Ciremai National Parks - Slamet Arif Susanto; Dianti Mayadika Putri; Ilma Rahmawati; Made Ari Sanjaya; Sulistijorini (Departemen Biologi, Institut Pertanian Bogor, 2021)
Water availability in Mount Ciremai National Parks (MCNP) is influenced by sustainability of the vegetation. Therefore, tree regeneration around the water springs area needs to be investigated to maintain the sustainability of water springs ecosystem in the future. The purpose of this study was to analyzed and identify natural seedlings of tree regeneration around the water springs area Seda Block MCNP. The collections of vegetation and abiotic data was carried out on 9 sample plots measuring 3 m × 3 m which is purposively placed around water springs. Result show that vegetation in water springs dominate by seedlings Ficus sp., Ficus hemsleyana, and Trevesia sundaica. Shannon-Weiner diversity index in this location was moderate, but evenness and dominance index classified as high and low, respectively. Overall, seedling of trees dominated by orthodox seed-type and shade tolerant plant. The vegetation in this study dominated by plants categorized least concern (LC) based on IUCN red list. Microclimatic of study site affects 58.89% on abundance and distribution of tree seedlings. Therefore, the springs are in the Seda Block MCNP needs to be conserved and maintain its natural vegetation. Keywords: Mount Ciremai National Park, eco-hydrology, canonical correspondent analysis, conservation